Ultratrace Detection of Nickel(II) Ions in Water Samples Using Dimethylglyoxime-Doped GQDs as the Induced Metal Complex Nanoparticles by a Resonance Light Scattering Sensor - Nipaporn Pimsin; Niradchada Kongsanan; Chayanee Keawprom; Phitchan Sricharoen; Prawit Nuengmatcha; Won-Chun Oh; Yonrapach Areerob; Saksit Chanthai; Nunticha Limchoowong (My University, 2021)
This study aimed to synthesize dimethylglyoxime (DMG) (N-source)-doped graphene quantum dots (N-GQDs) via simultaneous pyrolysis of citric acid and 1.0% (w/v) DMG. The maximum excitation wavelength (λ
Keywords: Dimethylglyoxime; Carbon and Quantum Dots Applications